Apocalyptic Pedagogies: Rethinking Publics and Publicness in the Time of Apocalypse - MacGill , Bindi (Journal of Public Pedagogies, 2022)
In this photo essay I draw on Haraway’s (2016) call to stay “with the trouble” and make “kin in the Chthulucene” to reflect on emergent community understandings as a result of catastrophic fires on Kangaroo Island (KI) in 2019. The title Immolation with Ashes is a signifier for staying with the trouble and draws on Indigenous ethics of care and understandings of connection to place. I draw on documentary photography that I conducted over several years on KI to unveil the impact of the ecological disaster and use the images as a site for reflection. Through the framing of apocalyptic pedagogies I offer a family vignette to provide insight into the event of the fires and the emergence of community knowledges and networks that arose as a result of the fires. The photos throughout the paper also reveal sites of healing landscapes in the same way in which traumatised communities form solidarity and knowledge in recovery.